2018
DOI: 10.1097/hjh.0000000000001598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium nitrite on renal function and blood pressure in hypertensive vs. healthy study participants

Abstract: This study demonstrated an augmented BP-lowering effect of NaNO2 in patients with EHT. We observed an antinatriuretic and antidiuretic effect of NaNO2 in both groups, and a decrease in U-ENaCγ, solely in EHT. In both groups, we detected a nonvasopressin mediated decrease in U-AQP2, which is most likely compensatory to the decline in diuresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In healthy adults, acute intravenous infusion of nitrite dose-dependently (0.58–5.21 μmol/kg/h) reduced blood pressure compared with placebo, but had no significant effect on GFR measured using 51 Cr-EDTA clearance 204 , 205 . This blood pressure response was augmented in hypertensive compared with normotensive individuals (mean decreases in systolic blood pressure of 17 mmHg vs 10 mmHg).…”
Section: Approaches To Restoring No Bioactivitymentioning
confidence: 96%
“…In healthy adults, acute intravenous infusion of nitrite dose-dependently (0.58–5.21 μmol/kg/h) reduced blood pressure compared with placebo, but had no significant effect on GFR measured using 51 Cr-EDTA clearance 204 , 205 . This blood pressure response was augmented in hypertensive compared with normotensive individuals (mean decreases in systolic blood pressure of 17 mmHg vs 10 mmHg).…”
Section: Approaches To Restoring No Bioactivitymentioning
confidence: 96%
“…Rosenbaek and colleagues showed that acute infusion of inorganic nitrite in healthy subjects, dose‐dependently increased sodium secretion, total urine volume, GFR and reduced blood pressure . In a recent randomized, placebo‐controlled, crossover study, these authors compared the blood pressure and renal function responses following infusion of nitrite (240 mg NaNO 2 kg −1 h −1 for 2 h) in hypertensive and healthy subjects . In this elegant study, it was evident that the nitrite‐mediated blood pressure‐lowering effect was more pronounced in hypertensive than in normotensive subjects (17 vs 10 mmHg, brachial systolic blood pressure).…”
Section: Therapeutic Value Of Stimulating the Nitrate–nitrite–no Pathwaymentioning
confidence: 99%